Ureteroneocystostomy Versus Ureteric Stenting for the Management of Ureterovaginal Fistula - Khalid Farouk, Riffat Najeeb , Mohibullah,Bushra Mohsin , Homera Riaz (Journal of Rawalpindi Medical College, 2014)
Background: To compare Ureteroneocystostomy versus ureteric stenting for the management of ureterovaginal fistula. Methods: This comparative study included patients with ureterovaginal fistulas . All the patients presented with history of urinary leakage. All of these patients had undergone abdominal hysterectomies. Detailed history revealed that these patients developed continuous leakage of urine starting 1-2 weeks postoperatively. All the patients had normal voiding along with continuous leakage of urine. A Foley’s catheter was passed through urethra and methylene blue was injected through the catheter into the bladder. Cystoscopy was carried out using 22Fr uretherocystoscope sheath and 30 degree telescope.Ureteric orifices were identified and a ureteric catheter size 5 Fr was introduced, under image intensifier. When an obstruction was noticed, no force was applied to push the ureteric catheter beyond obstruction. A ureteroscope of 7.5 Fr was introduced into the side showing obstruction. A guide wire was passed through the ureteroscope and an attempt was made to negotiate the guide wire beyond obstruction, up into the ureter, to the kidney.The position of the guide wire was confirmed by the fluoro image. As the guide wire was introduced successfully, a double J stent was advanced over the guide wire and placed in position under fluoro guidance. In cases where guide wire could not be negotiated beyond obstruction the procedure was converted to an open exploration and ureteric reimplantation. In these patients a unilateral low quadrant incision was made, and the ureter was traced extraperitoneally. The dilated ureter was identified and traced down towards the bladder up to the point where it was found buried in dense fibrosis and adhesions. Beyond this point as no healthy ureter could be traced so it was divided in an oblique manner, spatulated and ureteric reimplantation was carried out following Lich-Gregoir Technique over a 6 Fr ureteric stent . Intraoperative abdominal X Ray was done to confirm the place of stent. The ureteric stents were removed three months later in the patients who had successful endoscopic ureteric stenting. The patients having open ureteric reimplant had their stents removed after 3 weeks. Results: Endoscopic ureteric stenting was successful in six out of the twenty one cases. In the remaining cases, the patients underwent ureteric re-implant. In all the patients undergoing ureteric stenting urinary leakage stopped after the procedure. Ureteric stents were removed three months later with no complaints of urinary leakage upto six months follow up. All the thirteen patients who had ureteric re-implant became free of urinary leakage after surgery. These patients had an average post operative stay of 5 -7 days. In these patients ureteric stents were removed 3 – 4 weeks after ureteric reimplant. Follow up upto six months didn’t reveal any recurrence of urinary leakage. Conclusion: Endoscopic ureteric stenting should be considered the modality of choice for the management of Ureterovaginal fistula (UVF). It is minimally invasive, requires less hospital stay and is cost effective.